Confusion matrix for ensemble deep neural network illustrates the true positives, false positives, true negatives, and false negatives for each class. - Sadia Nazim (21440115) (2025)
Confusion matrix for ensemble deep neural network illustrates the true positives, false positives, true negatives, and false negatives for each class.